BIBLIOTECA NU E CĂRŢI - GHIURCO, Bogdan (BIBLIOPOLIS, 2020)
It is believed that libraries mean books and almost never – people. In 2016 it isn’t public relations courses or workshops offered by professional association and library formation centre. The most closest is the specialized course Techniques of public communication, offered by the National Association of Public Libraries and Librarians from Romania (ANBPR). Public relations are learned. The author presents several ways in which they could develop a training or a series of professional works.